Bibliometric Analysis: Using E-Modules Based on Project Based Learning in Physics Learning - Purnama Yani, Intan; Festiyed, Festiyed; Asrizal, Asrizal (Universitas Negeri Padang, 2024)
E-modules or electronic modules are modules in digital form, consisting of text, images, even both containing digital electronic material accompanied by simulations that can and are suitable for use in learning. The aim of this research is to see the extent of the development of research on e-modules based on project-based learning in Physics subjects. The research method used in this article is bibliometric analysis using VOSViewer software. The publication data comes from searches on the Publish or Perish software based on relevant keywords in Google Scholar indexed journals. There are 200 articles that are relevant to the keywords entered. Research on E-modules based on project-based learning needs to be improved to determine the level of success of students in mastering Physics lessons and project-based learning study topics have great potential to be explored and can be combined with various fields to make this research unique.